1985
DOI: 10.1111/j.1365-2621.1985.tb10490.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature, NaCI, and pH on the Growth of Aeromonas Hydrophila

Abstract: Growth of clinical isolates of Aeromonns hydrophila at various temperatures, pH values, and salt levels was studied in BHI broth. A majority of the isolates grew at 4-5°C and 42"C, and all grew equally well over the range 2G35"C. At 28"C, most isolates could tolerate 4% NaCl, while at 4°C only a limited number grew in 3% NaCl. Similarly, isolates could better tolerate acidic conditions when cultured at 28°C as compared to 4°C. These data suggest that it is likely that A. hydrophila strains associated with hums… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
5

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 27 publications
3
39
1
5
Order By: Relevance
“…hydrophila strains associated with human gastroenteritis are capable to grow in foods at refrigeration temperatures, currently considered adequate for preventing the growth of foodborne pathogens (Palumbo et al, 1985). Other authors reported wound infections in humans caused by A. hydrophila (Campbell, 2001;Hiransuthikul et al, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…hydrophila strains associated with human gastroenteritis are capable to grow in foods at refrigeration temperatures, currently considered adequate for preventing the growth of foodborne pathogens (Palumbo et al, 1985). Other authors reported wound infections in humans caused by A. hydrophila (Campbell, 2001;Hiransuthikul et al, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Three samples of chicken sausage from the lots that had contact with the water under investigation were also collected. The analyses of Aeromonas was conducted by counting in Starchampicilin Agar medium (Palumbo, Morgan, and Buchanan, 1985). The sample were serially diluted (10 -1 to 10 -5…”
Section: Methodsmentioning
confidence: 99%
“…was isolated by selective enrichment performed initially in tryptic soy broth (TSB) supplemented with ampicillin at a concentration of 30 milligrams per liter (ABEYTA JUNIOR et al, 1990). After incubation, the selective enrichment cultures were plated on phenol-amideampicillin red agar (PALUMBO et al, 1985) and ampicillin-dextrin agar (HAVELAAR & VONK, 1988), which were incubated again at 28°C for 24 hours and examined for the presence of large yellow colonies (3-5 mm) surrounded by a halo resulting from the hydrolysis of starch or dextrin, characteristics of Aeromonas. Up to five colonies were inoculated into tilted tubes of trypticase-soy agar (TSA) and, after confirming the presence of pure cultures; they were plated on triplesugar-iron (TSI) agar and subjected to the tests of motility, oxidase, catalase and resistance to the vibriostatic agent O/129 (POPOFF, 1984).…”
Section: Methodsmentioning
confidence: 99%